Relationship between ABO Blood group and Chronic Myeloid Leukemia with the Role of the Oxidative Stress as Risk Factor - Hassan, Abd AL Samed Uleiwi; Salih, Baneen Saleem; Alkati, Sami R aheem (International Journal of Psychosocial Rehabilitation, 2020)
Chronic myeloid leukemia characterized by the expansion of a clone of hematopoietic cells that carries the Philadelphia chromosome (Ph). The Ph chromosome results from a reciprocal translocation between the long arms of chromosomes 9 and 22, t (9;22). The aim of study are to find if there is an association between blood groups and chronic myeloid leukemia and to study some of the causes that may be lead to this association .Also , it aim to determine the role of the oxidative stress as risk factor. Ninety persons include in the study (45 as patient and 45 as control group). Where the patient suffering from CML, the control are free from this disease. There are ranged from (21-60) years old where they are divided in to four group according to blood group (A, B, AB, and O). This study is based in case control study done in the middle Euphrates center for cancer in Al-Najaf city from December 2018 to April 2019. The sera were collected from the 90 persons and analyzed by using enzyme linked immunosorbent assay (ELISA) for MDA and GSH. The results of the study show that blood group O (44%) predominates in CML patients group followed by blood group A (22%), B (18 %) and AB (16%). The mean serum level MDA value shows highly significance at (P˂0.001) change in the patients group in comparison with control. Also show that the level of MDA in male (900. 99 ± 603.89) is significantly higher than in female (582.28 ± 562.29). The mean serum level of GSH show that significant decrease at (P˂0.05) in patients group (40. 12 ± 27.33) than in control groups (55.20 ± 28.79). As a conclusion from this study, the importance of MDA and GSH in CML patients can be used to detect the complications related to the among these patients.